The Concept of Hiwalah And Dhomman In Islamic Teachings: a Comprehensive Study - Nur Aini Setyaningtyas; Abid Nurhuda; Dewi Sinta (MultiTech Publisher, 2023)
The essence of Islam is not only focused on the purity of worship but it must also be focused on social morality. This is by the Al-Qur'an and Hadith as the basis of Islamic teachings where much attention is paid to the 2 important things above. And one of the things that are paid attention to, especially in matters of social justice, is regarding debts and receivables which contain the concepts of hiwalah and dhomman, where these concepts are still not widely known by the public. This research aims to describe this. The method used is qualitative with a literature study approach and then concluded descriptively. The results of the research show that the concept of Hiwalah in Islamic teachings is the transfer of debt carried out by someone to another person on condition of willingness, agreement, the existence of collateral, there is an agreement between the two parties and there is a time limit so that the transfer of debt is legal, and it is impossible to be free from responsibility. The concept of Dhaman in Islam is to combine dzimah with others in the collection, whether with souls, debts, or other material substances while still fulfilling the pillars and conditions such as the existence of dhamin, madmun lah, madmun 'anhu, madmun bih, and lafadz so that the law can allow.